Critica dell’economia e critica della linguistica in Jean Baudrillard - Vaccaro, Giovambattista (Rivista Italiana di Filosofia del Linguaggio, 2016)
This essay shows the connexion between criticism of political economy and criticism of linguistics as parts of the revolutionary anthropology that the French philosopher and sociologist Jean Baudrillard aims to work out. Both of these criticisms are included in a general critical theory of value as exchange value of commodity in economics and exchange value of sign in semiotics, witch is the new form of  commodity in the affluent society. Both of these value forms reject the symbolic exchange, where no value in present. By this way this double criticism is the negative part of that anthropology, and the theory of the symbolic exchange the positive one. Baudrillard shows also the ways of the irruption of symbolic into the language in order to break its sequence and the signification relation. The most important of these ways is poetry, because poetical language breaks the order of discursive language. By thus way poetry is the most important form of revolution in language and has a political meaning inside the movements for human emancipation. In such theory Baudrillard is the last representative of a thought coming from surrealism through Henri Lefebvre and the Situationists and aiming to a total revolution of life.